Children playing outside the house - Mumbai Archive Project Team (Jio Institute, 2024)
Though the living quarters are small, one can feel the warmth that permeates closely-knit Koli homes. In Koli households, the concept of closed doors is virtually nonexistent. Neighbourhood children frequently visit and play, creating an atmosphere where the entire community feels like one big, extended household.